Коммутирующие расширения операторов - Арлинский, Ю.М.; Могилевский, В.И. (Український математичний журнал, 1993)
We obtain existence criteria and describe the commuting maximal proper extensions of a closed Hermite operator and a dual pair of continuous operators in a Hilbeit space.